Diversity of Coleopteran Insects at Horticulture Farmland in Pendem Village Batu City - Hastawulan, Anastassia Wita Aryandini; Rachmawati, Rina; Widjayanti, Tita (Journal of Tropical Plant Protection, 2025)
Coleopteran has a remarkable degree of environmental adaptation, allowing it to survive and reproduce in a variety of habitats. Research was conducted to determine the distribution of Coleopteran insects and the influence of commodities on the composition of Coleopteran insects. The research was conducted in May-August 2021 in Pendem Village, Batu City. Sampling is accomplished visually and through the placement of yellow pan traps and pitfall traps on tomatoes, large chili peppers, onions and cucumbers for 9 weeks. The study revealed 15 morphospecies belonging to the families Anthicidae, Carabidae, Chrysomelidae, Coccinellidae, Scarabaeidae, Staphylinidae, and Tenebrionidae which have roles as herbivore, predator and detritivore. In tomato plants 862 individuals were found, in large chili plants 1444 individuals were found, in onions plants 519 individuals were found and in cucumber plants, 697 individuals were found.